Эколого-морфологические особенности европейской лапи - Cervus (Dama) dama L.— в зоопарке «Аскания-Нова» - Кравченко, Р.С. (Вестник зоологии, 1971)
As a result of three-year observations of Cervus (Dama) dama L. in enclosures of the zoo it was established that main biological rhythms (shedding of horns, autumn anci spring moult, rut and calving) proceed in them for shorter periods of time than in other species of Cervus elaphus L. and depend on age, fatness and physiological state. Some peculiarities of Cervus (Dama) dama L. behaviour and the periods of biorhythms are described. The experience of Cervus (Dama) dama L. breeding in enclosures testifies to a high adaptability of the organism of these animals to the conditions of the South Ukraine.